Genotype by environment interaction and resource optimization in sugarcane variety evaluation in Swaziland - Dlamini, Njabulo Eugene (University of the Free State, 2016)
English: The primary aim of this study was to assess the genotype by environment interaction (GEI) in the sugarcane Variety Evaluation Programme (VEP) of the Swaziland Sugar Association (SSA). This was achieved by pursuing the specific objectives: to evaluate the adaptability and phenotypic stability of imported sugarcane genotypes in Swaziland; to determine the optimum combination of locations, replications and crop-years necessary to provide an adequate level of discrimination among genotypes within the SSA VEP; and to undertake a combined data analysis of irrigated sugarcane variety trials in Swaziland and South Africa. Data from replicated trials established across locations, seasons and crop-years were used, and the GenStat® 17th Edition software was used for the analyses. The study indicated that the main effects of variety, location and crop-years were significant, showing genetic diversity amongst the tested material and the complex environments under which they are tested. Consequently, these resulted in significant genotype by environment interactions (GEI). For sucrose yield, variety x location and variety x crop-year interactions were significant, while the higher order interaction (variety x location x crop-year) was not significant. Consistently, environments accounted for a larger portion of yield variation. The ratio of variety:GEI was largely dependent on the source of varieties. Varieties imported from Mauritius had a larger GEI effect than variety effect, while South African varieties had larger variety than GEI effects. This is attributed to the fact that conditions at which South African varieties are tested are similar to those in Swaziland. The grouping of test environments according to season clearly indicated that seasonal effects are stronger than location effects, as a result more emphasis should be put on testing across seasons than locations/soil types. Variety M1176/77 proved to be high yielding, stable and widely adapted to the sugarcane growing conditions of Swaziland, while M1400/86 was high yielding but specifically adapted to good draining soil conditions. To model the optimum number of locations, replications and crop-years necessary to provide adequate discriminating ability among varieties, the broad sense heritability was used. The results indicated that four locations, four replications per trials, and four crop-years were sufficient for variety testing within the industry. While the data used for the combined analysis of irrigated sugarcane variety trials of Swaziland and South Africa were largely unbalanced, the analysis indicated potential for SSA to utilise results from SASRI post-release trials to inform the industry’s variety recommendation. Both industries should consider pooling together testing resources and conduct variety evaluations at regional level. It is envisaged that making these adjustments will ensure that SSA derives maximum benefit from the resources used to test imported varieties.

Afrikaans: Die hoofdoel van hierdie studie was om genotipe by omgewing interaksie (GEI) in die suikerriet Cultivar Evaluasie Program (VEP) van die Swaziland Suiker Assosiasie (SSA) te bepaal. Dit is bereik deur spesifieke doelwitte: om die aanpasbaarheid en fenotipiese stabiliteit van ingevoerde suikerriet genotipes in Swaziland te bepaal; om die optimum kombinasies van lokaliteite, herhalings en gewas-jare te bepaal wat nodig is om ‘n goeie vlak van diskriminasie tussen genotipes binne die SSA VEP te kry; en om gekombineerde data analise van besproeide suikerriet cultivar proewe in Swaziland en Suid Afrika te doen. Data van gerepliseerde proewe oor omgewings, seisoene en gewas-jare is gebruik, en GenStat® 17th uitgawe sagteware is gebruik vir analise. Die studie het getoon dat hoofeffekte van cultivar, omgewing en gewasjare betekenisvol was, wat genetiese diversiteit in die getoetsde materiaal en die komplekse omgewings waar dit getoets is, getoon het. Dit het gevolglik gelei tot betekenisvolle genotipe by omgewings interaksies (GEI). Vir sukrose opbrengs, was cultivar x omgewing en cultivar x gewas-jaar interaksies betekenisvol, terwyl hoër vlak interaksie (cultivar x omgewing x gewas-jaar) nie betekenisvol was nie. Die omgewings het konstant vir ‘n groot deel van die variasie gesorg. Die verhouding van genotipe:GEI was grootliks afhanklik van die bron van die cultivars. Cultivars ingevoer vanaf Mauritius het ‘n groter GEI effek as cultivar effek getoon, terwyl Suid Afrikaanse cultivars groter cultivar as GEI effekte getoon het. Dit kan toegeskryf word aan die feit dat toestande waaronder Suid Afrikaanse cultivars getoets word, ooreenstem met toets-toestande in Swaziland. Die groepering van toetsomgewings volgens seisoen het duidelik getoon dat die seisoen effekte groter as omgewingseffekte was, daarom moet daar meer aandag gegee word aan toetsing oor seisoene as oor omgewings/grondtipes. Cultivar M1176/77 het hoë opbrengs gegee, was stabiel en wyd aangepas in die suikerriet groeitoestande van Swaziland, terwyl M1400/86 hoë opbrengs gegee het, maar spesifiek aangepas was vir grond met goeie dreinering. Om die optimum aantal omgewings, herhalings en gewas-jare te modeleer wat goeie diskriminasie tussen cultivars sal gee, is breë sin oorerflikheid gebruik. Die resultate het aangedui dat vier lokaliteite, vier herhalings per proef en vier gewas-jare genoeg was vir cultivar toetsing binne die industrie. Terwyl die data wat gebruik is vir die gekombineerde analise van besproeide suikerriet cultivar proewe van Swaziland en Suid Afrika grootliks ongebalanseerd was, het die analise die potensiaal vir SSA getoon om die resultate van SASRI se na-vrystellingsproewe te gebruik om industrie cultivar aanbevelings te maak. Die alternatief is dat beide industrië dit kan oorweeg om evaluasie hulpbronne bymekaar te gooi en om cultivar evaluasies op streek vlak te doen. Die verwagting is dat hierdie aanpassings sal sorg dat SSA maksimum voordeel trek uit die hulpbronne wat gebruik word om ingevoerde cutlivars te evalueer.
Keywords: Genotype by environment interaction; Resources; Sucrose; Sugarcane; Swaziland; Trials; Varieties; Yield; Sugarcane -- Breeding -- Swaziland; Sugarcane -- Swaziland -- Genetics; Dissertation (M.Sc.Agric. (Plant Sciences (Plant Breeding))--University of the Free State, 2016